Factorial Composition of the Questionnaire for Eudaimonic Well-Being (Qewb) in Mexican University Students - Garcia, Perla Jannet Jurado; Vega, Humberto Blanco; Perez, Jesus Enrique Peinado; Enriquez, Maria del Carmen Zueck (European Scientific Journal, ESJ, 2016)
The present study aims to provide empirical support for the factorial division Questionnaire adapted by Schutte et al. (2013) in a sample of women and men Mexicans adults. The total sample was of 1477 Mexican university students; 774 women and 703 men. The age ranged between 18 and 28 years (mean = 20.67 Â± 1.90 years). The factorial structure of the questionnaire was analyzed by 1) Exploratory factor analysis and 2) confirmatory factor analysis and factorial invariance. The factors of both subsamples showed adequate reliability and high congruence between pairs of factors, particularly considering the small number of items in each, resulting in a fully confirmatory model. However, the model obtained does not match fully with that proposed by Schutte et al. (2013).